Maternal Exposure to Quetiapine: Effects on Structural Changes in Developing Brain and its Lasting Impact on Neurobehavioral Impairments in Rat Offspring - P. Singh, Krishna; Tripathi, Nidhi (Current Psychopharmacology, 2014)
Reports on prenatal exposure to some first generation antipsychotic drugs like, haloperidol (HAL), and their effects on fetal neurotoxicity and functional impairments in the offspring are available; but studies on in utero exposure to second generation antipsychotics, especially quetiapine (QUE) and its effects on fetal neurotoxicity, neurobehavioral consequences, are lacking. Therefore, the present study was undertaken to evaluate the effect of prenatal administration to equivalent therapeutic doses of QUE on fetal brain size and weight, neuroarchitectural and neurohistopathological changes; and its long-lasting impact on neurobehavioral disturbances in youngadult offspring. Pregnant Wistar rats were exposed to selected doses (55 mg, 80 mg and 100 mg/kg) of QUE from gestation day (GD) 6-21 orally with control subjects. These doses were equivalent to human therapeutic doses of QUE. Half of the pregnant subjects of each group were sacrificed on GD 22 for histopathological studies and the rest of the dams were allowed to deliver normally. Their pups were reared postnatal up to 10 weeks of age for neurobehavioral observations. In prenatally QUE treated groups, substantial reduction in fetal brain size and weight, significant alterations in total neocortical thickness and in typical six layers of neocortex (cortical thinning), and loss of neuronal cells in the neocortex were found. Further, long-lasting impact of the drug was also observed on behavioral impairments in young-adult rat offspring. Therefore, QUE should be used with cautions to consider its developmental neurotoxicological and neurobehavioral potential in animal models, rat.
Keywords: prenatal